THE NEED TO USE INTERACTIVE TOOLS TEACHING TECHNOLOGIES IIRA FOR CRITICAL FORMATION THINKING OF ECONOMISTS (Pedagogy of Higher and Secondary Education, 2008)
It is the Article. An author is examine the aspects of forming of critical thought of economists on the basis of component-structural analysis of concept by recomm endations.
Keywords: critical thought; interactive technologies; preparation of economists